The physicochemical, nutritional, and sensory properties of cookies made with pumpkin flour - Seng, Gan Yong (Universiti Sains Malaysia, 2025)
Dietary habits play a crucial role in overall health, yet limited research has explored the impact of nutrient-dense cookies on consumer preferences. This study examined the use of pumpkin flour as a fat replacer to enhance the nutritional value of cookies while reducing their fat content. Pumpkin flour was produced in-house and incorporated into cookie formulations at substitution levels of 10%, 15%, 20%, and a control group. The cookies were analyzed for physicochemical properties, nutritional composition, and sensory attributes through panel evaluations. Substituting butter with pumpkin flour at a 20% level resulted in cookies with the highest carbohydrate content (70.42%) and ash content (1.07%), while maintaining similar protein levels, highlighting its potential to improve nutritional value. A 10% substitution level had minimal effects on aroma, taste, and overall acceptability, closely resembling standard cookies with slight differences in hardness, color, and appearance, making it a well-received option. Additionally, partially replacing butter with pumpkin flour significantly reduced the fat content of cookies, with levels decreasing from 37.0% in the control group to 29.7%, 28.25%, and 25.62% in the experimental groups (p < 0.05), underscoring its effectiveness as a fat-lowering alternative in baked products. Pumpkin flour's naturally high carbohydrate and fiber content contributed to increased moisture, ash, and carbohydrate levels, further demonstrating its effectiveness as a fat replacer. In conclusion, pumpkin flour can be effectively incorporated into cookies as a fat replacer, enhancing their nutritional profile without compromising sensory acceptability.